Hubungan Dukungan Sosial dengan Kesejahteraan Psikologis Mahasiswa Rantau : (Studi Deskripsi Korelasi pada Mahasiswa Baru Angkatan 2023 Prodi BK Universitas Sanata Dharma Yogyakarta) - Maria Rona Ayu Sekar Melati; Gendon Barus (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The research uses a quantitative correlational approach, with the subjects being 71 migrant students class of 2023 Guidance and Counseling Program. Data collection by distributing questionnaires through Google Form using a 28 items Social Support Scale with a Cronbach's Alpha value of 0.905 and a 40 items Psychological Well-being Scale with a Cronbach's Alpha value of 0,896.The results of the study indicate that (1) the level of social support of migrant students in the Guidance and Counseling Program class of 2023 is at a very high category, (2) the achievement of the social support scale score items that are less than optimal in 2 items (7%) in the medium category, (3) the level of psychological well-being of migrant students in the Guidance and Counseling Program class of 2023 is at a high category, (4) the achievement of the psychological well-being scale score items that are less than optimal in 5 items (13%) in the medium category, (5) there is a significant positive relationship between social support variable and psychological well-being with a value of r = 0.529 and a value of p = < 0.001 (p <0.05).